An admittance based hierarchical control framework for dual-arm cobots. (October 2022) - Tarbouriech, Sonny; Navarro, Benjamin; Fraisse, Philippe; Crosnier, André; Cherubini, Andrea; Sallé, Damien
Abstract: Dual-arm robotic platforms have solid arguments to match the growing need for versatility in the industry. Coupling the control of two manipulators for cooperative purposes enlarges the scope of feasible operations, while adding perception capabilities allows to navigate in dynamic environments. In this respect, we propose a complete online kinematic control framework for dual-arm robots operating in unstructured industrial settings. We base our approach on admittance control in the cooperative task space. Regulating internal and external efforts offer safe bimanual task execution and enables physical interaction. We implement a hierarchical quadratic programming architecture that applies a prioritization of tasks: most efforts are concentrated on the proper tracking of relative motions of the arms, which is the most critical for safety reasons. We demonstrate the performance of our framework through a "teaching-by-demonstration" experiment on the dual-arm mobile cobot BAZAR.